The simulation results of various modes of traction substations of DC - Andrienko, P. D.; Kaplienko, A. O. (Science and Transport Progress, 2008)
The model of direct current traction substation, with the subsequent carrying out on this model the research of electromagnetic processes on the substation in a mode of recuperation with energy absorption devices for inclusion of which contactless switches are used is developed. The modeling has allowed to estimate character of electromagnetic processes occurring on the traction substation at work of the absorbing device with contactless switches and to optimize the processes.